-(8y+2)-(7y-5)=-1

Simple and best practice solution for -(8y+2)-(7y-5)=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(8y+2)-(7y-5)=-1 equation:


Simplifying
-1(8y + 2) + -1(7y + -5) = -1

Reorder the terms:
-1(2 + 8y) + -1(7y + -5) = -1
(2 * -1 + 8y * -1) + -1(7y + -5) = -1
(-2 + -8y) + -1(7y + -5) = -1

Reorder the terms:
-2 + -8y + -1(-5 + 7y) = -1
-2 + -8y + (-5 * -1 + 7y * -1) = -1
-2 + -8y + (5 + -7y) = -1

Reorder the terms:
-2 + 5 + -8y + -7y = -1

Combine like terms: -2 + 5 = 3
3 + -8y + -7y = -1

Combine like terms: -8y + -7y = -15y
3 + -15y = -1

Solving
3 + -15y = -1

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -15y = -1 + -3

Combine like terms: 3 + -3 = 0
0 + -15y = -1 + -3
-15y = -1 + -3

Combine like terms: -1 + -3 = -4
-15y = -4

Divide each side by '-15'.
y = 0.2666666667

Simplifying
y = 0.2666666667

See similar equations:

| 9-1/2(3n-6)=n+2 | | 20n+4=24n-40 | | 2b+4=9+3b | | 5(x-2)=10(2-x) | | 0=z^2-(1+2i)z-x+2i | | 1+6x+3=5x+2 | | 0.5x^2-6=x^2+4x | | 4x+8+3x+9=13 | | f=-9+16 | | 15-8*2+12= | | -7p-4=-2p-14 | | 2[4-2(3-x)]-1=4[2(x-3)+7]-25 | | 99-4b=-11b | | 1+1+7a+3=a-1+4a | | .75k-.75=7 | | -8+b=4 | | x*5=x+4 | | 5x+45-3x=15 | | x+(x+5)+x+(x+5)=86 | | 2.25-.25g=.50g | | 5x+45+3x=15 | | 23x^2+22x=0 | | s^2=18-3s | | X+x+5+x+x+5=86 | | 23x+22x=0 | | (8p+4)+(9p+9)= | | 3+x=-8 | | a/5-1/5=-5 | | 1x+2=1x+3 | | 23.0*432*19= | | 9r^2+3r-30=0 | | 12x+2(5-2x)=6 |

Equations solver categories